A formação continuada do professor pedagogo no Programa de Desenvolvimento Educacional (PDE) - Lazaroto, Elaine (2021)
This thesis is bound to the line of research “Culture, Educational Processes, and Teacher Training” which studies the interrelationships between culture and education, teacher training and formal and non-formal educational processes in their theoretical-practical, sociopolitical, and pedagogical aspects. It is included in the Stricto Sensu Graduation Program in Education – Master’s degree – at the Western Paraná State University (UNIOESTE), in Francisco Beltrão, and is part of the study group of Higher Education, Training, and Teaching Work (GESFORT). Its topic is the continuing training of teachers, and its object is the continuing formation of teacher educators in the Education Development Program (EDP). The question to be answered is: To what extent the EDP, as a continuing training program, has contributed to the training of teacher educators in Regional Units of Education (RUE) of Dois Vizinhos, Francisco Beltrão, and Pato Branco cities? The aim is to analyze the EDP directed to teacher educators’ training bound to these units of South-west of Paraná state, Brazil. It uses a qualitative approach through bibliographic study, document and data analysis collected via questionnaire. The bibliographic study used works already published analyzing the social and political context from a critical and dialectical viewpoint, which states the educational phenomenon is marked by conflicts and contradictions. Regarding these contradictions in society, authors such as Ianni (2001) and Harvey (2008, 2017) are present in clarifying this research’s object. The document analysis is based on a set of federal and state legislations made of laws, decrees, ordinances, instructions, notices, data collection and studies available on official platforms. In this thesis’ analysis, the category of work and its implication in teacher training in the context of the 90s’ educational policies, in Brazil, are prominent. These policies have had an important role in teacher training. On continuing education in particular, courses were implemented without considering the actual needs of teachers coming from their school realities. In the 2000s, in the state of Paraná, during the administration of Requião Mello e Silva, through several studies showing fragmentation of continuing training courses, the state department of education (SEED) had proposed a program, the EDP in partnership with its department of science, technology and higher education. EDP was designed as a bold step, for it aimed to articulate theory and practice, and the return of teachers to higher education institutions. However, the present document analysis has shown that, throughout its eight editions, EDP has gone through a disassembly process in its curriculum, inserting topics of today over those related to the grounds of education, such as the increase in the distance workload. The answers submitted by respondents have shown that the EDP has contributed to teacher educator training. However, when this analysis is bound to the conception of an educator as the articulator of the pedagogical work, then it is was found incoherence in the understanding this conception. Other factors have influenced the training offered through EDP, as the discontinuity of research due to the intensification of pedagogical work, and the lack of encouragement in training policies that followed up EDP.